How Income Transfer Programs Affect Work, Savings, and the Income Distribution: A Critical Review - Danziger, Sheldon; Haveman, Robert; Plotnick, Robert D. (Journal of Economic Literature, 1981)
For helpful comments on earlier drafts, we thank, without implicating, Moses Abramovitz, Yves Balcer, John Bishop, Alan Blinder, Richard Burkhauser, Michael Darby, Irwin Garfinkel, Alan Gustman, Daniel Hamermesh, Martin Holmer, George Jakubson, Robert Lampman, Paul Menchik, Robert Moffitt, Michael Murray, Joseph Quinn, Timothy Smeeding, Eugene Smolensky, Barbara Wolfe and two anonymous referees.